Reduced inflammation in relapsing-remitting multiple sclerosis after therapy switch to rituximab. (12th July 2016) - de Flon, Pierre; Gunnarsson, Martin; Laurell, Katarina; Söderström, Lars; Birgander, Richard; Lindqvist, Thomas; Krauss, Wolfgang; Dring, Ann; Bergman, Joakim; Sundström, Peter; Svenningsson, Anders
Abstract : Objective: To describe the effects of switching treatment from ongoing first-line injectable therapies to rituximab on inflammatory activity measured by MRI and levels of CSF neurofilament light chain (CSF-NFL) in a cohort of patients with clinically stable relapsing-remitting multiple sclerosis (RRMS). Method: Seventy-five patients with clinically stable RRMS treated with the first-line injectables interferon-β (IFN-β) and glatiramer acetate (GA) at 3 Swedish centers were switched to rituximab in this open-label phase II multicenter study. After a run-in period of 3 months, 2 IV doses of 1, 000 mg rituximab were given 2 weeks apart followed by repeated clinical assessment, MRI, and CSF-NFL for 24 months. Results: The mean cumulated number of gadolinium-enhancing lesions per patient at months 3 and 6 after treatment shift to rituximab was reduced compared to the run-in period (0.028 vs 0.36, p = 0.029). During the first year after treatment shift, the mean number of new or enlarged T2 lesions per patient was reduced (0.01 vs 0.28, p = 0.004) and mean CSF-NFL levels were reduced by 21% ( p = 0.01). Conclusions: For patients with RRMS, a treatment switch from IFN or GA to rituximab is associated with reduced inflammatory activity measured by MRI and CSF-NFL. Classification of evidence: This study provides Class IV evidence that rituximab has an equal or superior effect in reducing inflammatory activity in RRMS measured by MRI and CSF-NFL compared to first-line injectables during the first year after treatment shift.